2016
DOI: 10.1038/cddis.2015.369
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming MITF-conferred drug resistance through dual AURKA/MAPK targeting in human melanoma cells

Abstract: MITF (microphthalmia-associated transcription factor) is a frequently amplified lineage-specific oncogene in human melanoma, whose role in intrinsic drug resistance has not been systematically investigated. Utilizing chemical inhibitors for major signaling pathways/cellular processes, we witness MITF as an elicitor of intrinsic drug resistance. To search kinase(s) targets able to bypass MITF-conferred drug resistance, we employed a multi-kinase inhibitor-directed chemical proteomics-based differential affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Accordingly, Vilgelm et al (2015) have shown that combined MDM2 and AURKA inhibition prolongs p53 activation and results in proliferation arrest, increased apoptosis, and immune clearance of melanoma cells. A promising therapeutic approach is the dual targeting of AURKA and MAPK inhibitors that leverages antiproliferative and apoptotic activities overcoming microphthalmia-associated transcription factor (MITF)econferred resistance to AURKA inhibitors (Pathria et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, Vilgelm et al (2015) have shown that combined MDM2 and AURKA inhibition prolongs p53 activation and results in proliferation arrest, increased apoptosis, and immune clearance of melanoma cells. A promising therapeutic approach is the dual targeting of AURKA and MAPK inhibitors that leverages antiproliferative and apoptotic activities overcoming microphthalmia-associated transcription factor (MITF)econferred resistance to AURKA inhibitors (Pathria et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…AURKA encodes Aurora kinase A, which is a serine/threonine kinase involved in mitotic spindle formation, centrosome separation, and G2/M phase transition during the cell cycle (D'Assoro et al 2016). Increased AURKA expression has been reported from nevi to primary and metastatic melanoma (Pathria et al, 2016;Wang et al, 2010), and its inhibition impairs cell proliferation and migration (Xie and Meyskens, 2013). Aurora kinase A overexpression is associated with either occurrence of metastasis (Reiter et al, 2006;Weier and Mao, 2013) or with shorter overall survival in nonmelanoma patients (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The association of AURKA inhibitors with microtubule stabilisers (taxanes) showed promising results [138][139][140][141]. The AURKA inhibitor MLN8054 (a precursor of Alisertib) or Alisertib itself, in combination with the BRAF inhibitor GSK2118436 and the MEK inhibitor GSK1120212, was shown to have a supplementary anti-proliferative effect in 2D and 3D in cellulo models of melanoma [142,143]. However, cell proliferation was not totally abolished and a small fraction of actively proliferating cells were retrieved in the dermal stratum of 3D cultures, indicating their resistance to drugs.…”
Section: Aurka and Drug Resistancementioning
confidence: 99%
“…However, the mechanism of action of MITF is rather complex: low or absent levels of this protein predispose cells to apoptosis; intermediate MITF expression levels promote cell proliferation and survival; high concentration of intracellular MITF proteins induces antiproliferative effects [ 85 ]. An association was reported between MITF overexpression, partially regulated by AurkA, and MAPK pathway activation in controlling melanoma cell proliferation and migration [ 86 ]. MITF amplification was found in 5.0% of CMs, regardless of the BRAF/RAS mutational status (Table 3 ).…”
Section: Mitfmentioning
confidence: 99%